Mendayung di Permukaan: Kritik Narasi Politik Jelang Pilihan Presiden 2024 - Felisianus Novandri Rahmat; Yohanes Baptista Pendamai Marut (Universitas Merdeka Malang, 2023)
The battle for political narratives ahead of the 2024 presidential election still leads to negative narratives such as issues of SARA, identity politics, hoaxes, black propaganda which cause polarization and division. The research intends to criticize this narrative so that the implementation of the 2024 election will run in a conducive and peaceful manner. The research method is a literature study on several articles that discuss political messages contained in narratives, campaigns or other political communication activities. Based on the findings, it seen that negative narratives have the potential to be reused in future contests. Elites need to be encouraged to work together and build a shared commitment to conduct political education, offer ideas and programs, reduce hoaxes, create new positive jargon and hashtags and design creative campaigns on social media. It creates politeness, mutual respect and foster civility as well as to reduce negative narratives in the public sphere upcoming presidential election contest.Â Â